Model Sistem Penyelenggaraan Pemberian Makanan Tambahan (PMT) Balita melalui Program Rumah Gizi Sehat (PROGES) - Humayrah, Wardina; Nuraelah, Almira; Febrina, Laila (Indonesian Journal for Social Responsibility, 2025)
The Healthy Nutrition House Programme (PROGES) was implemented by Sahid University (USAHID) to improve the nutritional quality of young children at risk of stunting and malnutrition in RW 06, Pancoran Mas, Depok City. This programme focuses on creating a sustainable supplementary feeding system model (PMT) by engaging community members as donors. The first phase of PROGES successfully involved 30 participants from all RW06 residents and community leaders from the Integrated Service Post (Posyandu) and Family Empowerment and Welfare (PKK) cadres. Prior to the socialisation of the programme, the participants were asked several questions through a questionnaire regarding their initial views on the programme, which consisted of: experiences with the programme, types of food usually donated for PMT for young children, main reasons for participating in the programme, and perceptions of benefits if implemented for the RW 06 community. This was followed by a Forum Group Discussion (FGD) to agree on a PMT implementation system model that would meet the needs of the residents. The results of the FGD for the PMT implementation system model started with data collection on the recipients of donations, identification of donors, and collection of food ingredients from the residents, which were then stored in the Healthy Nutrition House RW 06 according to cooked or raw conditions. In addition, food distribution is carried out once a month before Posyandu, with priority given to underprivileged households with malnourished young children at risk of stunting. This first phase of the PROGES programme went smoothly and a sustainable PMT system model was successfully agreed with community leaders and residents of RW 06.